(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study assessed the status of cooperative learning strategies at Haramaya University, focusing on the College of Education and Behavioral Sciences. A qualitative research design was employed, utilizing interviews, focus group discussions (FGDs), and observations for data collection. The study involved 80 participants, including students from four departments, department heads, the college dean, and the Academic Assessment and Quality Assurance director. Third-year students were specifically chosen for their relevant experience with cooperative learning. Findings indicated that the implementation of cooperative learning strategies has significantly declined and become ineffective since the COVID-19 outbreak. Key factors contributing to this decline included distancing policies, lack of commitment, instructor workload, additional administrative duties, student interest, time constraints, inadequate supervision, lack of awareness, poor classroom facilities, and insufficient support. The study emphasizes the importance of cooperative learning for enhancing student performance, suggesting that students benefit from peer learning at their own pace rather than solely from instructors. It calls for all stakeholders, including students and administrative bodies, to prioritize the effective practice and implementation of cooperative learning strategies.